1970
DOI: 10.1677/joe.0.0480001
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role for the Adenyl Cyclase System in Calcitonin Release

Abstract: A possible role of the adenyl cyclase system in calcitonin (CT) release has been investigated by measurement of the rate of CT secretion in isolated porcine thyroid glands perfused in situ. Dibutyryl cyclic AMP increased the rate of secretion of CT and this effect was enhanced by theophylline. Concentrations of glucagon as low as 1\m=.\4nm (5 ng/ml) induced a significant increase in the rate of CT secretion when precautions were taken to prevent enzymic degradation of glucagon. This stimulatory effect of gluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…The enhancement of calcitonin secretion with glucagon, an activator of the adenyl cyclase system in other tissues (19,20), theophylline, an inhibitor of phosphodiesterase (27), and dibutyryl cyclic 3',5'-adenosine monophosphate suggests that secretion can be augmented by increasing the concentration of cyclic 3',5'-adenosine monophosphate in the parafollicular cells of the thyroid gland. These studies with regard to the adenyl cyclase system and calcitonin secretion are in agreement with preliminary findings carried out in vivo (28).…”
Section: Discussionsupporting
confidence: 90%
“…The enhancement of calcitonin secretion with glucagon, an activator of the adenyl cyclase system in other tissues (19,20), theophylline, an inhibitor of phosphodiesterase (27), and dibutyryl cyclic 3',5'-adenosine monophosphate suggests that secretion can be augmented by increasing the concentration of cyclic 3',5'-adenosine monophosphate in the parafollicular cells of the thyroid gland. These studies with regard to the adenyl cyclase system and calcitonin secretion are in agreement with preliminary findings carried out in vivo (28).…”
Section: Discussionsupporting
confidence: 90%
“…These results were obtained with pharmacologic doses of CT and PTE, but Ardaillou et al (13) reported a significant increase of UCa in human subjects who were given an infusion with only 0.4 MRC U porcine CT/hr. This figure approaches measured hormone quantities secreted in the pig (37). Hence, our data might have physiological significance.…”
Section: Discussionsupporting
confidence: 59%
“…It has been similarly noted that the prevailing serum calcium level does not solely regulate parathyroid hormone [PTH (5)] or calcitonin [CT (6,7)] secretion. A variety of in vivo and in vitro studies indicate that the secretion of PTH and CT may be influenced in animals by two groups of neuroendocrine modulators, catecholamines (8)(9)(10)(11)(12)(13) and prostaglandins (14)(15)(16). Previous data suggested that secretion of PTH is augmented in humans by /?-adrenergic stimulation (17,18).…”
mentioning
confidence: 99%